(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Ocimum kilimandscharicum is a short herb, native to India. In traditional medicine, it is used to treat various ailments including colds, coughs, abdominal pains, measles and diarrhea. Medicative plants, the “back bone” of ancient medication which implies over 3.3 billion folks within the less developed countries utilize medicative plants on an everyday basis. Ocimum kilimandscharicum Guerke (Syn. Ocimum camphora Guerke) belongs to family Lamiaceae. It is a native of Kenya and distributed in East Africa, India, Thailand, Uganda and Tanzania. It is extensively grown in the Tropics. In India it is cultivated on a small scale, especially in West Bengal, Assam, Tamil Nadu, Karnataka, Kerala and Dehradun. .The present study is aimed to evaluate in vitro anti-inflammatory, assessment was carried out on the basis of parameters such as heat induced protein denaturation, heat induced haemolysis, and Hypotonicity induced haemolysis. The standard drug was Diclofenac sodium. The findings of the present study showed that the 500 µg/ml of Ethanolic extraction of Ocimum kilimandscharicum ( EEOK) showed more percentage inhibition when compared to standard. On the basis of results, it can be concluded that Ethanolic extraction of Ocimum kilimandscharicum (EEOK) showed significant anti- inflammatory activity.